Where is Settler Colonialism? - Cameron, Emilie (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2026)
This essay considers both the limits and necessity of mobilizing settler colonial frameworks in the contemporary moment. It traces the rise of Settler Colonial Studies as the dominant framework for making sense of colonial relations in Canada and considers the limits of this framework for understanding colonization in Inuit Nunangat, where the settler state’s interest in dispossession, extraction, and proletarianization have played out differently than in southern Canada. Guided by Aimé Césaire’s directive to ask, again and again, what colonization is, I consider why Settler Colonial Studies frameworks are so readily mobilized in the study of northern Canada but are hyperpoliticized when they are applied to Israel/Palestine, why Inuit theories of colonization barely figure in Qallunaaq research about the North, and what this means for theorizing colonialism in the current conjuncture.